2020
DOI: 10.1074/jbc.ra120.013530
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of ASH1L histone methyltransferase in anaplastic thyroid carcinoma

Abstract: Anaplastic thyroid cancer (ATC) is one of the most aggressive human malignancies, with an average life expectancy of ∼6 months from the time of diagnosis. The genetic and epigenetic changes that underlie this malignancy are incompletely understood. We found that ASH1-like histone lysine methyltransferase (ASH1L) is overexpressed in ATC relative to the much less aggressive and more common differentiated thyroid cancer. This increased expression was due at least in part to reduced levels of microRNA-200b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 66 publications
0
20
2
Order By: Relevance
“…However, the results obtained from this study are based on a small sample series in need of experimental validation. For example, our findings of overexpressed hsa-miR-200b-3p in TERT promoter mutated FTCs are in conflict with the previously demonstrated down-regulation in ATCs, thereby serving as a good example for a miRNA candidate reliant on further analyses using larger tumor cohorts as well as the inclusion of normal controls [9].…”
contrasting
confidence: 99%
“…However, the results obtained from this study are based on a small sample series in need of experimental validation. For example, our findings of overexpressed hsa-miR-200b-3p in TERT promoter mutated FTCs are in conflict with the previously demonstrated down-regulation in ATCs, thereby serving as a good example for a miRNA candidate reliant on further analyses using larger tumor cohorts as well as the inclusion of normal controls [9].…”
contrasting
confidence: 99%
“…It is located at chromosome 8q24.21, and is in the vicinity of the proto-oncogene c-MYC (51). CCTA1 has (52). These prior experimental data strongly suggest that CCTA1 exhibits oncogenic behavior in TC.…”
Section: Colon Cancer-associated Transcript-1 (Ccat1)mentioning
confidence: 85%
“…lncRNA are RNAs longer than 200 nucleotides that do not encode proteins but regulate gene expression, splicing and nucleation of subnuclear domains [49]; moreover, lncRNAs may have cytoplasmic functions, such as miRNA sponging, interaction with signaling proteins, and further modulation of mRNA translation [49]. In ATC, lncRNAs may regulate tumor growth [84,85], invasiveness [86], and both tumor growth and invasiveness [87][88][89][90][91]; they can also regulate cancer sensitivity to treatments [92]. In particular, lncRNA PTCSC3 was described at low levels both in ATC tissue and cell lines and it was demonstrated that its upregulation inhibited the resistance to doxorubicin by suppressing stem cell proprieties [92].…”
Section: Cell Growth Invasivenessmentioning
confidence: 99%